AAA-ATPases in Protein Degradation - Yedidi, Ravikiran S.; Wendler, Petra; Enenkel, Cordula (Frontiers in Molecular Biosciences, 2017)
Proteolytic machineries containing multisubunit protease complexes and AAA-ATPases play a key role in protein quality control and the regulation of protein homeostasis. In these protein degradation machineries, the proteolytically active sites are formed by either threonines or serines which are buried inside interior cavities of cylinder-shaped complexes. In eukaryotic cells, the proteasome is the most prominent protease complex harboring AAA-ATPases. To degrade protein substrates, the gates of the axial entry ports of the protease need to be open. Gate opening is accomplished by AAA-ATPases, which form a hexameric ring flanking the entry ports of the protease. Protein substrates with unstructured domains can loop into the entry ports without the assistance of AAA-ATPases. However, folded proteins require the action of AAA-ATPases to unveil an unstructured terminus or domain. Cycles of ATP binding/hydrolysis fuel the unfolding of protein substrates which are gripped by loops lining up the central pore of the AAA-ATPase ring. The AAA-ATPases pull on the unfolded polypeptide chain for translocation into the proteolytic cavity of the protease. Conformational changes within the AAA-ATPase ring and the adjacent protease chamber create a peristaltic movement for substrate degradation. The review focuses on new technologies toward the understanding of the function and structure of AAA-ATPases to achieve substrate recognition, unfolding and translocation into proteasomes in yeast and mammalian cells and into proteasome-equivalent proteases in bacteria and archaea.